The Foundation of Innovation: A Purpose-Driven Approach - Malpangotti, Stefano (Digital Repository of Theses - SSBM Geneva, 2025)
This study introduces Purpose-Driven Innovation (PDI), as a comprehensive managerial framework designed to unify theory and practice. PDI offers a practical tool for aligning organizational innovation with an organization’s mission and core values, fostering a unified and purpose-driven approach. PDI demonstrates that purpose and innovation are deeply interconnected, driving new entrepreneurial perspectives. By embedding purpose into every aspect of strategy, PDI transforms innovation into a purposeful endeavor, encapsulated in the Purpose Articulation Statement, a dynamic tool that redefines traditional Mission Statements. The framework consists of eight interlinked nodes, balancing creative exploration with disciplined execution and employing holistic strategies to drive meaningful and sustainable outcomes. A pilot case study of Netflix tested the framework, leading to the addition of a ninth node to emphasize the critical importance of continuous renewal and adaptation. PDI equips organizations with a practical and comprehensive blueprint to foster creativity, enhance operational efficiency, and build resilience. By staying true to their core values, organizations can effectively navigate complexity, adapt to change and create lasting value in a rapidly evolving world. This research offers a clear roadmap for organizations to turn purpose and innovation into a powerful competitive advantage within a fair and equitable society.